INTEGRASI METODE PEMBAYARAN QRIS DALAM MENDUKUNG LITERASI KEUANGAN DIGITAL MENUJU INDONESIA EMAS 2045 - Pancawati, Anom Pancawati Ni Luh Putu; Sudarma, I Made; Somiartha, I Putu (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2025)
Digital informatioan requires its users to adapt, understand, and be able to use applications by utilizing various digital infrastructures, one of which is the QRIS payment method. This research aims to explain the adoption of the integration of the QRIS payment method and its supporting and inhibiting factors in promoting digital financial literacy towards Indonesia Emas 2045. The research method uses a qualitative approach. The results show that the adoption of QRIS as a payment method has great potential in supporting the understanding of digital finance, which not only facilitates payment transactions but also strengthens the foundation for digitalization changes. Factors such as convenience and accessibility, data privacy and security, contactless transactions, marketing and promotion, as well as the prevention of counterfeit currency, drive adoption. Conversely, the gap ini technology infrastructure ownership, lack of technological knowledge, dependence on cash availability, limited internet access, and security issues due to QR code fraud hinder adoption. Cooperation between the community, government, private sector, and financial institutions is needed to determine strategic steps to continuously improve and enhance the use of the QRIS payment menthod in supporting digital-based financial literacy and to contibute to human development and mastery of science and technology.